The Middle Ages Revisited - Jervis, Ben (Archaeopress, 2018)
This volume, produced in honour of Professor David A. Hinton's contribution to medieval studies, re-visits the sites, archaeologists and questions which have been central to the archaeology of medieval southern England. Contributions are focused on the medieval period (from the Anglo-Saxon period to the Reformation) in southern England.